MODEL BARU PENGEMBANGAN KARYAWAN ADMINISTRATIF DI PERGURUAN TINGGI SWASTA: INTEGRASI TEKNOLOGI DAN KOMPETENSI SOFT SKILLS - Wiyono, Darul; Ambiapuri, Ema; Ekawati Permana, Tatiek (Universitas Prof. Dr. Hazairin SH, 2024)
This research aims to explore the influence of Technology Integration and Soft Skills Competence on the Development of Administrative Staff in Private Higher Education Institutions in Bandung. In the modern era marked by technological advancements and the complexity of job demands, this study is relevant for examining how the integration of technology and the development of soft skills competence can affect administrative staff in higher education institutions. The research methodology adopts a quantitative approach with a Total Population of 414 employees from 138 institutions, and a sample of 203 employees selected through Area Probability Sampling. Data collection is conducted using a questionnaire, and data analysis is performed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that both Technology Integration and Soft Skills Competency have a positive and significant influence on the development of administrative staff, with the Mediating Effect of Development Model Effectiveness playing a pivotal role. Limitations of the study include potential constraints on generalization within the context of private higher education institutions in Bandung. The research contributes by providing strategic recommendations to enhance technology integration, develop soft skills competencies, and design effective development models for administrative human resources. These findings are expected to serve as a foundation for efforts to improve the performance and development of administrative staff in higher education institutions.